2017
DOI: 10.1371/journal.pone.0178626
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug events—Analysis of a decade. A Portuguese case-study, from 2004 to 2013 using hospital database

Abstract: PurposeThe goal of this study was to characterise adverse drug events (ADE), including both adverse drug reaction (ADR) and accidental poisoning by drugs (AP), considering age, gender, length of stay (LOS), number of deaths and year, during the period 2004–2013. Additionally distributions of the ten’s most frequent ADR and AP were characterized, considering age-group and gender.MethodsA retrospective descriptive nationwide study was conducted, based on the hospital discharges database in Portugal from 2004 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 51 publications
3
15
0
3
Order By: Relevance
“…Regarding the class of drugs associated with in-hospital ADEs, we observed that the antineoplastic/immunosuppressant drugs were among the most frequent causes of events, similar to other studies carried out at a national and international levels 4,5,10,18 . Antibiotics, adrenal cortical steroids, anticoagulants, and diuretics not elsewhere specified were also included among the five most frequent causes of ADEs.…”
Section: Cad Saúde Pública 2020; 36(3):e00056519supporting
confidence: 87%
See 3 more Smart Citations
“…Regarding the class of drugs associated with in-hospital ADEs, we observed that the antineoplastic/immunosuppressant drugs were among the most frequent causes of events, similar to other studies carried out at a national and international levels 4,5,10,18 . Antibiotics, adrenal cortical steroids, anticoagulants, and diuretics not elsewhere specified were also included among the five most frequent causes of ADEs.…”
Section: Cad Saúde Pública 2020; 36(3):e00056519supporting
confidence: 87%
“…The most recent Portuguese studies, based on administrative data, showed an ADE frequency of between 1.46% and 1.88% 10,11,21 , but they also did not differentiate between the ADE present at the time of admission and the in-hospital one.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In Norway, older people (aged 67 years or above) account for almost 60% of the 149,551 patients receiving HHN each year [14]. This patient group is especially vulnerable to adverse events because they often have complex care needs caused by multimorbidity, polypharmacy, and multiple functional limitations [6,[15][16][17][18]. In addition, the risks to older patients in their own homes are rather different from those in institutions, e.g., different environment, roles, and failure to monitor over long periods.…”
Section: Introductionmentioning
confidence: 99%